FOXC1-mediated serine metabolism reprogramming enhances colorectal cancer growth and 5-FU resistance under serine restriction - Zhukai Chen; Jiacheng Xu; Kang Fang; Hanyu Jiang; Zhuyun Leng; Hao Wu; Zehua Zhang; Zeyu Wang; Zhaoxing Li; Mingchuang Sun; Ziying Zhao; Anqi Feng; et al. (Cell Communication and Signaling)
Abstract Colorectal cancer (CRC) is the most common gastrointestinal malignancy, and 5-Fluorouracil (5-FU) is the principal chemotherapeutic drug used for its treatment. However, 5-FU resistance remains a significant challenge. Under stress conditions, tumor metabolic reprogramming influences 5-FU resistance. Serine metabolism plasticity is one of the crucial metabolic pathways influencing 5-FU resistance in CRC. However, the mechanisms by which CRC modulates serine metabolic reprogramming under serine-deprived conditions remain unknown. We found that exogenous serine deprivation enhanced the expression of serine synthesis pathway (SSP) genes, which in turn supported CRC cell growth and 5-FU resistance. Serine deprivation activate the ERK1/2-p-ELK1 signaling axis, leading to upregulated FOXC1 expression in CRC cells. Elevated FOXC1 emerged as a critical element, promoting the transcription of serine metabolism enzymes PHGDH, PSAT1, and PSPH, which in turn facilitated serine production, supporting CRC growth. Furthermore, through serine metabolism, FOXC1 influenced purine metabolism and DNA damage repair, thereby increasing 5-FU resistance. Consequently, combining dietary serine restriction with targeted therapy against the ERK1/2-pELK1-FOXC1 axis could be a highly effective strategy for treating CRC, enhancing the efficacy of 5-FU.